Assessment of safety and efficiency of nitrogen organic fertilizers from animal‐based protein hydrolysates—a laboratory multidisciplinary approach. (12th July 2013) - Corte, Laura; Dell'Abate, Maria Teresa; Magini, Alessandro; Migliore, Melania; Felici, Barbara; Roscini, Luca; Sardella, Roccaldo; Tancini, Brunella; Emiliani, Carla; Cardinali, Gianluigi; Benedetti, Anna
Abstract BACKGROUND Protein hydrolysates or hydrolysed proteins (HPs) are high‐N organic fertilizers allowing the recovery of by‐products (leather meal and fluid hydrolysed proteins) otherwise disposed of as polluting wastes, thus enhancing matter and energy conservation in agricultural systems while decreasing potential pollution. Chemical and biological characteristics of HPs of animal origin were analysed in this work to assess their safety, environmental sustainability and agricultural efficacy as fertilizers. Different HPs obtained by thermal, chemical and enzymatic hydrolytic processes were characterized by Fourier transform infrared spectroscopy and sodium dodecyl sulfate polyacrylamide gel electrophoresis, and their safety and efficacy were assessed through bioassays, ecotoxicological tests and soil biochemistry analyses. RESULTS HPs can be discriminated according to their origin and hydrolysis system by proteomic and metabolomic methods. Three experimental systems, soil microbiota, yeast and plants, were employed to detect possible negative effects exerted by HPs. The results showed that these compounds do not significantly interfere with metabolomic activity or the reproductive system. CONCLUSION The absence of toxic and genotoxic effects of the hydrolysates prepared by the three hydrolytic processes suggests that they do not negatively affect eukaryotic cells and soil ecosystems and that they can be used in conventional and organic farming as an important nitrogen source derived from otherwise highly polluting by‐products. © 2013 Society of Chemical Industry